2012
DOI: 10.1007/s10567-012-0123-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Intervention for Foster Parents of Young Foster Children with Externalizing Behavior: Theoretical Basis and Program Description

Abstract: Foster parents are often faced with serious externalizing behaviors of their foster child. These behavioral problems may induce family stress and are related to less effective parenting and often increase. Foster children with behavioral problems are also more at risk of placement breakdown. An intervention to support foster parents of young foster children with externalizing behaviors is necessary to improve the effectiveness of foster placements. Based on research on effective parenting interventions and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 53 publications
1
25
0
2
Order By: Relevance
“…Enrollment and attendance rates in this pilot study are promising; our enrollment rate for eligible families (22/48) in this hard-to-reach population compares positively with rates found in recent trials in foster care (Chamberlain, Price, Leve, Laurent, Landsverk, & Reid, 2008; Vanschoonlandt, Vanderfaeillie, Van Holen, & De Maeyer, 2012). Attendance rate across intervention components (73%) demonstrated program engagement for this hard-to-reach population.…”
Section: Discussionsupporting
confidence: 55%
“…Enrollment and attendance rates in this pilot study are promising; our enrollment rate for eligible families (22/48) in this hard-to-reach population compares positively with rates found in recent trials in foster care (Chamberlain, Price, Leve, Laurent, Landsverk, & Reid, 2008; Vanschoonlandt, Vanderfaeillie, Van Holen, & De Maeyer, 2012). Attendance rate across intervention components (73%) demonstrated program engagement for this hard-to-reach population.…”
Section: Discussionsupporting
confidence: 55%
“…Positive associations have been found between parenting stress, child externalizing as well as child internalizing problem behaviour (Johnston & Mash ; Ashford et al ; Rodriguez ). Despite the fact that parenting stress is an indicator rather than a cause of parenting problems, it has been identified as an important target for intervention in its own right in relation to child behavioural problems and prevention of child maltreatment (Rodriguez & Richardson ; Ashford et al ; Neece & Baker ; Vanschoonlandt et al ). It is still unknown whether IAB and DSEB are associated with parenting stress in young children, referred with emotional and behavioural problems.…”
Section: Introductionmentioning
confidence: 99%
“…; Vanschoonlandt et al . ), they can trigger an escalation of mutually coercive behaviour between foster parents and child.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, what emerges is an escalating chain of mutually coercive interactions between foster parents and foster child (Vanschoonlandt et al . ). Research has also found that internalizing behaviour on the part of the child produces greater insecurity among foster parents, leading them to resort to harsher and less consistent punishments (Vanderfaeillie et al .…”
mentioning
confidence: 97%
See 1 more Smart Citation